The relationship between the national football league scouting combine and game performance over a 5-year period - Cook, J.; Ryan, G. A.; Snarr, R. L.; Rossi, S. (The Journal of Strength and Conditioning Research, 2020)
There has been doubt on the ability of the National Football League (NFL) Scouting Combine to predict successful future game performance. This study analyzed data from athletes who participated in the Combine between 2013 and 2017 (n = 1,537) and their subsequent year's performance in the NFL. Data from 6 athletic measures were normalized for each athlete when compared with all other athletes (avgCZ) and athletes of the same position (avgPZ). Correlational analysis was used to ascertain whether the physical performance tests were associated with subsequent year's game performance (avgS). A multiple linear regression was performed to examine whether individual event Combine performance could predict the subsequent year's avgS in the NFL. Of the 35 correlations found when examining relationships, only 2 correlations were found to be moderately strong, avgCZ—avgS2 (r = 0.320), avgPZ—avgS2 (r = 0.332), whereas most were found to be weak (r < 0.3). Furthermore, data analysis suggests that Combine measures can only explain approximately 2.6% of the variance in avgS 1 year after the Combine when using 3 (vertical jump, bench press, and PRO) performance tests as predictors. The primary results of this study suggest that the NFL Combine lacks predictive ability when examining first year game performance. Furthermore, it also lacks correlational strength when examining relationships between performance and subsequent 5-year performance in the NFL. Caution should be used if coaches, general managers, and other front office staff are considering the use of Combine data as a possible selection for the upcoming NFL Draft.